The Dynamic Conformational Cycle of the Group I Chaperonin C-Termini Revealed via Molecular Dynamics Simulation - Dalton, Kevin M.; Frydman, Judith; Pande, Vijay S. (PLOS ONE, 2015)
Chaperonins are large ring shaped oligomers that facilitate protein folding by encapsulation within a central cavity. All chaperonins possess flexible C-termini which protrude from the equatorial domain of each subunit into the central cavity. Biochemical evidence suggests that the termini play an important role in the allosteric regulation of the ATPase cycle, in substrate folding and in complex assembly and stability. Despite the tremendous wealth of structural data available for numerous orthologous chaperonins, little structural information is available regarding the residues within the C-terminus. Herein, molecular dynamics simulations are presented which localize the termini throughout the nucleotide cycle of the group I chaperonin, GroE, from Escherichia coli. The simulation results predict that the termini undergo a heretofore unappreciated conformational cycle which is coupled to the nucleotide state of the enzyme. As such, these results have profound implications for the mechanism by which GroE utilizes nucleotide and folds client proteins.